2002
DOI: 10.1046/j.1365-2249.2002.01999.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 ameliorates the outcome ofStaphylococcus aureusarthritis by promoting bacterial clearance

Abstract: Summary Staphyllococcus aureus‐induced infections often result in high mortality and permanent joint destruction, despite treatment with antibiotics. IL‐10 is typically regarded as an anti‐inflammatory cytokine because it promotes a T helper cell type 2 response, and subsequently down‐regulates cell mediated immune functions. To investigate the role of IL‐10 in S. aureus‐induced arthritis and sepsis, Balb/c mice, intact or defective with respect to IL‐10 gene were intravenously inoculated with bacteria. IL‐10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 32 publications
2
30
1
Order By: Relevance
“…It has been already suggested that lack of IL-10 causes impaired bacterial clearance leading to more destruction in septic arthritis [73]. Our data indicated that S. aureus infection led to reduction in IL-10 level both in serum and synovial tissues due to higher levels of proinflammatory cytokines which might interfere with the release of IL-10.…”
Section: Discussioncontrasting
confidence: 40%
“…It has been already suggested that lack of IL-10 causes impaired bacterial clearance leading to more destruction in septic arthritis [73]. Our data indicated that S. aureus infection led to reduction in IL-10 level both in serum and synovial tissues due to higher levels of proinflammatory cytokines which might interfere with the release of IL-10.…”
Section: Discussioncontrasting
confidence: 40%
“…29 In support of this is the finding that IL-10 is needed for efficient elimination of some bacteria. 30 IL-10 plays a central role in infectious diseases, particularly in balancing between destruction and protection, which is the most essential of its many functions. 27 There have been few studies of the role of IL-10 in spirochetal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of an animal model of septic arthritis have shown that IL-10 has antiinflammatory effects (25). To study whether plasmin has any effects on IL-10 expression during bacterial arthritis, Western blot analysis was performed to compare IL-10 levels in Plg ϩ/ϩ and Plg -/-mice.…”
Section: Persistent Inflammation and Tissue Destructionmentioning
confidence: 99%